A Study of the Production and Marketing of Onion in the Tripoli Area - EL-WIFATI, BASHIR; NAWAS, FARID (The Libyan Journal of Agriculture, 2023)
This study was conducted in the months of February and March, 1978, to identify and find out feasible solutions for the major production and marketing problems facing onion growers in the Tripoli area. Ninety-three farmers from Al-Aziziah, Azzahra, Suany, Naseria, and Janzur areas where interviewed and asked to till out a questionaire designed to fulfill the objectives of this study. The study showed that all sampled farmers grew onions. However, different farmers allocated different areas to the production of onions. The study also revealed that most onion seeds available in the local markets were imported from abroad. ‘Thalatha Wholesale Market’ in Tripoli was the main marketing outlet for the majority of the farmers. Besides, the study indicated that cleaning, storage, and packaging of onions was done on the farm before marketing. Farmers, also expressed concern about the predetermined low’ prices of onions and recommended that prices of either green or dry onion crops should be raised. The majority of the sampled farmers felt that there is an urgent need for more and adequate cold storage facilities since this might solve the surplus problem and reduce price fluctuations. A deep concern was also expressed about the need for more help to be extended by the agricultural extension service and agricultural cooperatives in the area under investigation.